2009
DOI: 10.5194/acp-9-7343-2009
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent observations of air pollutants at two sites in the Pearl River Delta and the implication of regional transport

Abstract: Abstract. An intensive field measurement study was conducted simultaneously at a site within the inland Pearl River Delta (PRD) region (WQS) and a site in Hong Kong (TC) between 22 October and 1 December 2007. Ambient air pollutants measured included O 3 , NO x , CO, SO 2 , NMHCs, and carbonyls. The purpose is to improve our understanding of the interplay among local and regional air pollutants in the Hong Kong area, and the influence of regional transport on local air pollutants. The results indicate that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
134
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(152 citation statements)
references
References 49 publications
18
134
0
Order By: Relevance
“…Studies have shown that cities in this region suffer from regional air pollution [11][12][13]. As one class of persistent organic pollutants, PAHs can undergo long range atmospheric transport.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that cities in this region suffer from regional air pollution [11][12][13]. As one class of persistent organic pollutants, PAHs can undergo long range atmospheric transport.…”
Section: Introductionmentioning
confidence: 99%
“…The local anthropogenic emissions were thus not significant, with most air pollutants originating from the surrounding cities. The site was 50 km southeast of Guangzhou center, 40 km southwest of Dongguan, 50 km northwest of Shenzhen, and 25 km northeast of Zhongshan, making it a good regional station to characterize the air pollution of the inner PRD (Guo et al, 2009). The PM 2.5 high-volume samplers (Tisch Environmental Inc., USA) were placed on the rooftop of a building, about 30 m above the ground.…”
Section: Field Samplingmentioning
confidence: 99%
“…Trends of O 3 and its precursors with a p value < 0.05 were considered significant (Guo et al, 2009). …”
Section: Measurement Techniquesmentioning
confidence: 99%
“…Hong Kong, together with the inland Pearl River Delta (PRD) region of southern China, has suffered from high O 3 mixing ratios in recent years (Chan et al, 1998a, b;Wang and Kwok, 2003;Ding et al, 2004;Zhang et al, 2007;Guo et al, 2009Guo et al, , 2013. In 2014, O 3 exceeded the Chinese national air quality standard (80 ppbv, for the daily 8 h maximum average, DMA8) on more than 90 days in some areas of the PRD, with the highest DMA8 value of 165 ppbv (GDEMC and HKEPD, 2015).…”
Section: Introductionmentioning
confidence: 99%